Sweetened beverages, snacks and overweight: findings from the young lives cohort study in Peru - Alviso Orellana, Claudia Lorena (2018)
Objective: To determine the association between consumption of snacks and sweetened beverages and risk of overweight among children. Design: Secondary analysis of the Young Lives cohort study in Peru. Setting: Twenty sentinel sites from a total of 1818 districts available in Peru. Subjects: Children in the younger cohort of the Young Lives study in Peru, specifically those included in the third (2009) and the fourth (2013) rounds. Results: A total of 1813 children were evaluated at baseline; 49•2 % girls and mean age 8•0 (SD 0•3) years. At baseline, 3•3 (95 % CI 2•5, 4•2) % reported daily sweetened beverage consumption, while this proportion was 3•9 (95 % CI 3•1, 4•9) % for snacks. Baseline prevalence of overweight was 22•0 (95 % CI 20•1, 23•9) %. Only 1414 children were followed for 4•0 (SD 0•1) years, with an overweight incidence of 3•6 (95 % CI 3•1, 4•1) per 100 person-years. In multivariable analysis, children who consumed sweetened beverages and snacks daily had an average weight increase of 2•29 (95 % CI 0•62, 3•96) and 2•04 (95 % CI 0•48, 3•60) kg more, respectively, than those who never consumed these products, in approximately 4 years of follow-up. Moreover, there was evidence of an association between daily consumption of sweetened beverages and risk of overweight (relative risk=2•12; 95 % CI 1•05, 4•28). Conclusions: Daily consumption of sweetened beverages and snacks was associated with increased weight gain v. never consuming these products; and in the case of sweetened beverages, with higher risk of developing overweight.